The influence of preheating temperature on the mechanical properties of injection-overmolded hybrid glass fiber reinforced thermoplastic composites - Fu, Liang; Zhang, Muhan; Zhai, Zhanyu; Jiang, Fengze (Polymer Testing, 2022)
Thermoplastic overmolding technique is an advanced integrated manufacturing technology to fabricate hybrid fiber reinforced thermoplastic composites (hybrid composites) components in which short fiber reinforced thermoplastics are injected onto the surface of thermoformed continuous fiber reinforced thermoplastic (CFRT) laminate (organosheet). To further clarify the bonding mechanism between the heterogeneous interface of short and continuous glass fiber reinforced thermoplastic composites, a series of experimental tests and molecular dynamic (MD) simulations were conducted to investigate the preheating temperature of organosheet on mechanical properties of hybrid composites. The experimental results reveal that the surface roughness of organosheet is increased with raising the preheating temperature, resulting in the enhancement of mechanical interlock at the bonding interface. The interface region in SEM observation is gradually disappeared due to molecule diffusion. Simulation results show that both diffusion coefficient and interfacial bonding energy are clearly improved with preheating temperature. Compared with the non-preheating condition, the flexural strength of the hybrid composite is increased by more than three times when the preheating temperature is set as 220 degrees C by IR heater. Moreover, the fracture mode of hybrid composites has been proven to change with the preheating temperature.
CRIS-Team WoS Importer:2021-12-10